Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
(x-7)^2 + (y+3)^2 = 49
Step-by-step explanation:
The general equation for a circle is given by
(x-h)^2 + (y-k)^2 = r^2
where ( h,k) is the center and r is the radius
(x-7)^2 + (y- -3)^2 = 7^2
(x-7)^2 + (y+3)^2 = 7^2
(x-7)^2 + (y+3)^2 = 49
Answer;
(x-7)^2 + (y+3)^2 = 49
Step-by-step explanation:
The general equation for a circle is given by
(x-h)^2 + (y-k)^2 = r^2
where ( h,k) is the center and r is the radius
(x-7)^2 + (y- -3)^2 = 7^2
(x-7)^2 + (y+3)^2 = 7^2
(x-7)^2 + (y+3)^2 = 49
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.